2018
DOI: 10.3389/fimmu.2018.02897
|View full text |Cite
|
Sign up to set email alerts
|

Immune Correlates of Natural HIV Elite Control and Simultaneous HCV Clearance—Supercontrollers

Abstract: HIV-elite controllers are a minority group of HIV-infected patients with the ability to maintain undetectable HIV viremia for long time periods without antiretroviral treatment. A small group of HIV-controllers are also able to spontaneously clear the hepatitis C virus (HCV) whom we can refer to as “supercontrollers.” There are no studies that explore immune correlates looking for the mechanisms implicated in this extraordinary phenomenon. Herein, we have analyzed HCV- and HIV-specific T-cell responses, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Other T cells that notably differed between old and young subjects were CD161+ T cells. These cells mainly produce IL-17 and are known to have an important contribution in pathogen clearance (Dominguez-Molina et al, 2018). CD161+ T cells presented higher levels in young people comparing with old ones, independently on the vaccination (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other T cells that notably differed between old and young subjects were CD161+ T cells. These cells mainly produce IL-17 and are known to have an important contribution in pathogen clearance (Dominguez-Molina et al, 2018). CD161+ T cells presented higher levels in young people comparing with old ones, independently on the vaccination (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…CD161+ T cells has been associated with IL-17 production and hence with pathogen clearance (Merino et al, 2021). In fact, we have previously observed that CD161+ CD8+ T cells were related with HIV and hepatitis C virus (HCV)-specific T cells polyfunctionality, which is essential for HIV spontaneous control and HCV spontaneous clearance (Dominguez-Molina et al, 2018). Results presented herein suggest CD161 marker as a hallmark of T cell immunosenescence in accordance with recent findings, which show a correlation of CD161 expression on CD8+ T cells with age independently of CMV infection (Formentini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these subjects were PWID and had multiple re‐exposures to HCV during the first years of being positive that mainly occurred in the 80s and early 90s and anti‐VHC and HCV RNA measurements were later available, if after all this re‐exposures the individual remained with negative ARN for HCV tell us about the preserved ability of those subjects to spontaneously clear the virus. We believe that independently the individuals became positive with one virus before the other, normally HCV precedes HIV positivity and the potential re‐exposures to HCV, it will be interesting to extent immunological correlates [23] of persistent HIV control and HCV spontaneous clearance to deeply dissect the intrinsic host mechanisms involved in this extraordinary phenotype. We have recently found that these subjects, able to clear HCV and spontaneously control HIV, referred as “supercontrollers,” showed higher levels of HCV‐specific CD4 + T‐cell polyfunctionality, higher levels of CD8 + CD161 T‐cells together with low T‐cell exhaustion associated with preserved innate immunity features [23].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that independently the individuals became positive with one virus before the other, normally HCV precedes HIV positivity and the potential re‐exposures to HCV, it will be interesting to extent immunological correlates [23] of persistent HIV control and HCV spontaneous clearance to deeply dissect the intrinsic host mechanisms involved in this extraordinary phenotype. We have recently found that these subjects, able to clear HCV and spontaneously control HIV, referred as “supercontrollers,” showed higher levels of HCV‐specific CD4 + T‐cell polyfunctionality, higher levels of CD8 + CD161 T‐cells together with low T‐cell exhaustion associated with preserved innate immunity features [23]. This sustained immunity is also reflected in the rates of HCV spontaneous clearance in these subjects (25.5%) which is similar to that found in HCV monoinfected patients in Spain (22%) [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation